LIPID PROFILE IN SMOKING - Akbari, M. Zamir Ahmad; Bhatti, Muhammad Sarwar; Shakoor, Muhammad (Journal of Ayub Medical College Abbottabad, 2000)
Background: Smoking is one of the major risk factors in the genesis of coronary atherosclerosis and development of coronary heart disease. Smoking which is recognized as a major risk factor for the development of ischaemic heart disease may lead to alter the normal plasma lipoprotein pattern. Methods: Fifty adult smokers were selected along with thirty normal controls. Lipid profile was studied and estimations of cholesterol, total lipids, triglycerides. HDL. LDL. VLDL and chylomicrons were made. Results: All these parameters except HDL level were significantly increased in smokers while HDL level was significantly decreased, showing greater risk of these persons to atherosclerosis and coronary heart disease (CHD). Various ratios like LDL/HDL. VLDL/HDL. TG/HDL and TC/HDL were calculated to find out the risk of atherosclerosis and CHD so that early measures could be adopted to avoid complicated disease process.